Factors Favouring Neonatal Mortality in the Masisi Health Zone, 2020-2021 - SHUKURU KASIWA, Benjamin; MAHAMBA BANYENE, Beatrice; BAUMA BALINGENE, Alex; MUNFANO LUKONGE, Justin; DUSABE BAREB, Deborah (European Journal of Science, Innovation and Technology, 2023)
Introduction. It is an obvious principle that a newborn should not die from unknown or preventable causes. To achieve this, it is useful to investigate the reasons why in terms of factors favouring neonatal deaths within the population. Method. This study was carried out in Masisi among patients and staff at the Masisi GRH; it is both descriptive and cross-sectional, using purely quantitative data. Two target populations constituted the sample size for this study, the first consisting of 12 medical staff in the neonatology department and the second of women of childbearing age, i.e. a sample of 84 persons. The data were collated using a survey questionnaire distributed to the two populations. Results. After analysing, processing, tabulating and interpreting the data, we came to the following findings. Referring to the medical and health factors at the root of neonatal deaths, the results of this study indicate that a large proportion (83.3%) of respondents said that women did not fully attend prenatal consultations; among them 40% had an attendance frequency of two out of four times compared with 10% who did not attend at all. More than half of children (58.3%) are born with the combined weight categories. Regarding the socio-economic factors favouring neonatal deaths, 59.5% of respondents eat what they find during the gestation period against a minority (3.6%) who eat vegetables the most. Hence the two emerging hypotheses of this study were affirmed. Conclusion. Women of childbearing age should be strengthened in prenatal education and take care of advice they receive; women should support the initiatives of the family planning programme by their adherence and abandon negative cultural practices. Health professionals should continue to meet the social, medical and health care needs of children in the neonatology department.